2012
DOI: 10.1352/1944-7558-117.5.349
|View full text |Cite
|
Sign up to set email alerts
|

Social Interactions of Students with Disabilities Who Use Augmentative and Alternative Communication in Inclusive Classrooms

Abstract: The purpose of this study was to explore the naturally occurring social interactions for students with disabilities who use augmentative and alternative communication (AAC) in general education classrooms. We observed 16 students who used AAC and received services under the categories of autism or intellectual disability. Participants primarily interacted with their support personnel and infrequently conversed with peers despite often being in close proximity. Few interaction episodes were initiated by student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 42 publications
5
88
0
1
Order By: Relevance
“…given the ongoing growth of the aaC research base and the need for practitioners to access information regarding evidence-based practice, there is a pressing need for articles synthesizing the aaC literature (schlosser & sigafoos, 2009). an increasing number of systematic reviews have recently appeared in the aaC literature and include those focusing on such topics as reading instruction (barker, saunders, & brady, 2012), peer interactions (Chung, Carter, & sisco, 2012), autism (ganz et al, 2012schlosser & Wendt, 2008), challenging behaviors (Walker & snell, 2013), tangible symbol use (roche et al, 2014), and facilitated communication (schlosser et al, 2014). given the presence of the growing body of evidence investigating the use of partner instruction in aaC, there is a need to summarize and synthesize this body of work as well, which is the focus of the present article.…”
Section: Synthesis Articles In Aacmentioning
confidence: 99%
“…given the ongoing growth of the aaC research base and the need for practitioners to access information regarding evidence-based practice, there is a pressing need for articles synthesizing the aaC literature (schlosser & sigafoos, 2009). an increasing number of systematic reviews have recently appeared in the aaC literature and include those focusing on such topics as reading instruction (barker, saunders, & brady, 2012), peer interactions (Chung, Carter, & sisco, 2012), autism (ganz et al, 2012schlosser & Wendt, 2008), challenging behaviors (Walker & snell, 2013), tangible symbol use (roche et al, 2014), and facilitated communication (schlosser et al, 2014). given the presence of the growing body of evidence investigating the use of partner instruction in aaC, there is a need to summarize and synthesize this body of work as well, which is the focus of the present article.…”
Section: Synthesis Articles In Aacmentioning
confidence: 99%
“…Children with complex communication needs and cerebral palsy did not show significant differences from typically developing peers when mastery motivation pleasure was considered along with task persistence, even though maternal support behaviors were fewer for the children with complex communication needs than for peers (Wang, Morgan, Hwang, Chen & Liao, 2014). Given that successful communication in children with complex communication needs necessitates the mastery motivation to work hard in interaction to overcome communicative turn imbalance with partners (Chung et al, 2012;Clarke & Wilkinson, 2009), it is encouraging that children showed their best skills using social-based mastery motivation behaviors that are integral to the social communication process (e.g., attending to partners, conveying messages, and showing enjoyment with partners).…”
Section: Effect Of Motor Skills On Mastery Motivationmentioning
confidence: 90%
“…Children with complex communication needs may initiate assertively less often or use fewer turns than peers in classroom interaction (Chung, Carter, & Sisco, 2012) and task-based conversations (Clarke & Wilkinson, 2009) in home, school and play contexts, though this imbalance in turns can become less prevalent when they reach adulthood (Lund & Light, 2007). However, children with complex communication needs do not show unbalanced turns or passive communication strategies in all contexts.…”
Section: Introductionmentioning
confidence: 99%
“…When students with IDD are physically in the room but not included as full and participating members of the class they are more likely to be viewed as visitors and to lack friendships with peers (Jorgensen et al, 2006;Schnorr, 1990). Additionally, educator proximity can be a barrier to friendship formation, especially by paraprofessionals (Giangreco, 2010), as students tend to interact with individually assigned adults rather than peers (Chung, Carter, & Sisco, 2012).…”
Section: Parent and Teacher Perspectives On Friendships And Social Inmentioning
confidence: 99%